Occurrence and Preventability of Adverse Drug Events in Hospitalized Patients: A Systematic Review - ., Suherman; Nurwahyuni, A (KnE Life Sciences, 2018)
Patient safety is now recognized as a priority by health systems around the world, drug-related problem is one of the component for patient safety assessment. The objective of this study is to systematically review the occurrence and preventability of Adverse Drug Events in hospitalized patients. This study uses systematic review based on the Prisma Protocol. A search was conducted on electronic databases such as ProQuest, SpringerLink, and Scopus using relevant keywords. The relevant studies were further selected using inclusion and exclusion criteria. Three studies were included in this review, two of which were research study by group and one was a dissertation study. All studies were conducted in hospitals. From the three journals, it can be seen that the incidence of ADE occurs in nearly all hospitals studied and that drug-related problems are still a significant burden for healthcare facilities. Adverse Drug Events are relevant problems in hospitalized patients. The occurrence of ADE was confirmed in all studies and ADE less can be prevented by the use of CPOE. Keywords: adverse drugs events, medication-related problem, adverse drug reaction reporting system, hospitalized patients